Profile of female deaths by homicide in the city of Goiânia - Luana Muzzi Vaz David; Ruth Minamisava; Priscila Valverde de Oliveira Vitorino; Maria José Pereira Rocha; Viviane Santos Mendes Carneiro; Maria Aparecida da Silva Vieira
ABSTRACT Objectives: to identify the female homicide profile in the city of Goiânia. Methods: a cross-sectional, descriptive study that characterized female deaths by homicide from 2008 to 2015. They occurred in Goiânia, and registered in the Mortality Information System. Cases of homicide of women aged ≥ 10 years were eligible. Other causes of death were excluded. Descriptive statistical analysis with frequencies. Results: three hundred seventy-six women died from assault, with an increase in the percentage of deaths annually. Most of the victims were young (57.5%), single (78.8%), mixed-ethnicity (61.1%) and with low education (58.4%). The most frequent means of assault was firearm (64.0%). The health districts with the highest record of female deaths due to assault were southwest, center and northwest. Conclusions: the predominant profile of women victims of femicide was young, mixed-ethnicity, single, with low level of education and living in less favored regions.